Partisipasi perempuan dalam ranah politik di Indonesia: Pemilu - Mauliya, Dewi Farhana (Maliki Interdisciplinary Journal, 2023)
Indonesia is a democratic country that upholds democratic values in every decision-making process. This article aims to explore the extent of women’s participation in Indonesia within the context of a deeply rooted patriarchal culture in society. This patriarchal culture tends to prioritize or elevate men above women. As a result, women often feel overlooked, which impacts their confidence to engage or play a role in the political arena. In this research, the method used is literature review, involving the analysis of existing literature. There is hope that women’s participation in politics will continue to increase, despite the prevailing patriarchal culture. The involvement of women in politics is crucial, as women also have the potential to occupy strategic positions in the political world. Therefore, continuous efforts are needed to ensure that women receive equal opportunities and can contribute to political decision-making.